2023
DOI: 10.1002/saj2.20488
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evaluation of in‐season Y Drop applications for corn production

Abstract: A common strategy for improving fertilizer N uptake efficiency by corn (Zea mays L.) is to synchronize application with crop N demand during the growing season, which can be done using the Y Drop system recently developed for surface dribble placement. A 2‐yr field study was conducted using dual‐labeled urea‐ammonium nitrate (UAN) solution to compare fertilizer 15N uptake efficiency (F15NUE) for surface and subsurface sidedress applications to soils of contrasting fertility under either second‐year corn or a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…For both growing seasons studied, dry matter production without fertilization was consistent with what was observed for overlapping site‐years in other 15 N studies aimed at evaluating fall applications of anhydrous NH 3 (Griesheim et al., 2019) or in‐season placement of UAN (Griesheim et al., 2022). Consistencies were also observed when comparing grain yields from fertilized plots with county‐level data, which averaged slightly lower in 2017 (11.3 Mg ha −1 ) than in 2021 (11.5 Mg ha −1 ) when expressed on a dry‐weight basis (https://www.nass.usda.gov).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For both growing seasons studied, dry matter production without fertilization was consistent with what was observed for overlapping site‐years in other 15 N studies aimed at evaluating fall applications of anhydrous NH 3 (Griesheim et al., 2019) or in‐season placement of UAN (Griesheim et al., 2022). Consistencies were also observed when comparing grain yields from fertilized plots with county‐level data, which averaged slightly lower in 2017 (11.3 Mg ha −1 ) than in 2021 (11.5 Mg ha −1 ) when expressed on a dry‐weight basis (https://www.nass.usda.gov).…”
Section: Resultssupporting
confidence: 84%
“…In this analysis, a KMnO 4 ‐Fe pretreatment was modified as described by Griesheim et al. (2022) to control frothing during a series of heating steps ramping from 90°C to 350°C in a block digester (Seal Analytical Model BD50). The digest was alkalized for diffusion with 10 M NaOH, and the NH 4 + ‐N liberated was quantified by acidimetric titration and then analyzed for 15 N content using an automated mass spectrometer (Mulvaney et al., 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the dominance of soil N uptake that has been documented in numerous 15 N field studies with corn (Cerrato & Blackmer, 1990; Griesheim et al., 2023; Power et al., 1986; Schindler & Knighton, 1999; Stevens et al., 2005) and the 112 kg ha −1 application of unlabeled N that was supplied at planting, NDFSU was expected to exceed NDF 15 F at R6. This was indeed observed for every plant part analyzed in our work, as Tables 6 and 7 show a range of 63% to 89% for NDFSU and 11% to 37% for NDF 15 F.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the dominance of soil N uptake that has been documented in numerous 15 N field studies with corn (Cerrato & Blackmer, 1990;Griesheim et al, 2023;Power et al, 1986;Schindler & Knighton, 1999;Stevens et al, 2005) and the f Data reported as a mean from triplicate plots. Means within a column followed by the same letter do not differsignificantly (p < 0.05).…”
Section: Crop Uptake Of Soil-and Fertilizer-derived Nmentioning
confidence: 99%